Magic Realism as a Postcolonial Discourse in Marquez’s One Hundred Years of Solitude and Rushdie’s Midnight’s Children - Sharma, Khum Prasad (Literary Studies, 2015)
This study analyzes and explores the concept of magic realism as a mixture of realism and fantasy made in order to serve a particular artistic fusion. The mixture is based on the fact that whatever happens, however extraordinary they may seem, they are ordinary and everyday occurrences. Anything which takes place within the boundaries of magical realism is meant to be accepted as a typical life among the characters in the stories. No matter how far-fetched or extraordinary the subjects may be, all the characters within the works give an allusion of acting naturally and casually. Instead of looking at the world as ordinary and mundane, the magical realists like Marquez and Rushdie bring in a spark of imagination to light the ordinary experiences such a way that they excite the mind of the readers. Magical realism is a fusion of dream and reality, an amalgamation of realism and fantasy, and a form of expression that is based with several fantastical elements, which are nevertheless regarded as normal by both the readers and the characters. This artistic device re-imagines the world and its reality, and presents a different viewpoint on life and the way in which people think and act. Marquez and Rushdie present the worlds where fiction blends with historical reality and in which reality incorporates magic, superstition, myth, religion and history. They use magical elements to create, rewrite and reconstruct broader commentaries on the politics, history and societies in Latin America and India. Marquez and Rushdie employ and establish an alternative reality which juxtaposes fantastical elements with equally mind boggling realities; the truth becomes fantasy and the fantasy becomes truth to disclose historical and political panorama of Latin America and India respectively.